Cytotoxic effect on human cancer cell using SRB method (in vitro) rimpang temu mangga (Curcuma Mangga Val. & V. Zijp.) dan kunir putih (Curcuma Zedoaria I.) - Mae Sri Hartati W, Mae Sri Hartati W (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2003)
Background: Temu mangga (Curcuma mangga) and kunir putih (Curcuma zedoaria) rhizomes have been utilized by people to treat cancer lately although clinically their activity has not been tested. Objectives: This study is aimed to prove their activity as anticancer on 7 major human cancers cell lines (in vitro), and to evaluate whether these two rhizomes are potential for new anticancer drug. Methods: The two rhizomes were separately extracted with chloroform followed by methanol to give chloroform extracts of C. mangga (CmCh) and C. zedoaria (CzCh); and methanol extracts of C. mangga (CmMe) and C. zedoaria (CzMe) respectively. These extracts were tested their cytotoxic effect on 7 major human cancer cell lines using SRB method (in vitro). Doxorubicin and cisplatin were used as positive controls, and their cytotoxic effects were measured by comparing their ID50 with that of the positive controls.Results: Those four extracts (CmCh, CzCh, CmMe and CzMe) practically did not perform cytotoxic effect on those human cancer cell lines, because the extract's ID50 was far higher than the positive controls on those human, cancers cell linesConclusion: The C. mangga and C. zedoaria rhizomes did not active as anticancer and they were not pOtential as the source of a new anticancer drug.Key words: anticancer - Curcuma mangga - Curcuma zedoaria - cytotoxic - drug discovery